Social traps and the problem of trust - Rothstein, Bo. (Cambridge Cambridge University Press, 2005)
Bo Rothstein explores how social capital and social trust are generated and what governments can do about it. A 'social trap' is a situation where individuals, groups or organizations are unable to cooperate owing to mutual distrust and lack of social capital, even where cooperation would benefit all. Examples include civil strife, pervasive corruption, ethnic discrimination, depletion of natural resources and misuse of social insurance systems. Much has been written attempting to explain the problem, but rather less material is available on how to escape it.
Includes bibliographical references (p. 212-235) and index.
Keywords: Social capital (Sociology)